Lipidomics: PTFI Platform - Williams, Kevin; Odenkirk, Melanie T; Watkins, Steve; Brinkley, Sarah (2025)
The PTFI Lipidomics platform enables targeted lipid characterization in food and/or biological samples. It employs Bligh-Dyer1 extraction for lipid isolation and Sciex QQQ or qTRAP instrumentation with differential mobility spectrometry (DMS) and multiple reaction monitoring (MRM) for absolute quantification.